PENGEMBANGAN MEDIA PENGUKUR VOLUME BENDA BERBENTUK TIDAK TERATUR BERBAHAN WADAH MINUMAN BEKAS PADA MASA “PTMT” - RR. INDAH WAHJU RATNAWATI (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2021)
This study aims to produce a product in the form of a medium for measuring the volume of irregularly shaped objects, made from used drink containers. The type of media developed is in the form of practical aids. This research includes development research known as Research and Development. During the limited face-to-face learning period (PTMT) the learning process must be designed as effectively as possible, because students study at school for only about 4 hours, without rest. The existence of practical aids is very helpful for students' understanding of the concepts explained by the teacher, but not all schools have laboratory equipment that is proportional to the number of students. To overcome this problem, a solution is given to develop a practical tool made from used drink containers for measuring the volume of irregularly shaped objects. Before the practical aids were tested, they were validated by material experts and material experts. The average results of the two validation experts. obtained a score of 97.05% with a very decent category. The media trial included a limited test consisting of 12 students of class VII/B and a broad test which was carried out on all students of class VII/B of 32 students. The results of the limited test obtained an average of 98.3%, and in the broad test an average of 99% was obtained with a very decent predicate as well. After the trial, the students were given a set of test tools in the form of questions related to the material for measuring the volume of objects with irregular shapes. The results of the tests completed by students after using the developed media, students who scored above the KKM were 96%, this indicates that the developed media is feasible to use and can help students understand the concept of measuring the volume of irregularly shaped objects. ABSTRAKPenelitian ini bertujuan untuk menghasilkan produk berupa media pengukur volume benda yang berbentuk tidak teratur, berbahan wadah minuman bekas. Jenis media yang dikembangkan berupa alat bantu praktik. Penelitian ini termasuk penelitian pengembangan yang dikenal dengan istilah Research and Development. Pada masa pembelajaran dengan tatap muka terbatas (PTMT) proses pembelajaran harus di rancang seefektif mungkin, karena siswa belajar di sekolah hanya sekitar 4 jam, tanpa istirahat. Keberadaan alat bantu praktik sangat membantu pemahaman siswa terhadap konsep yang dijelaskan guru, namun tidak semua sekolah memiliki peralatan laboratorium yang sebanding dengan jumlah siswa. Untuk mengatasi masalah tersebut diberikan solusi mengembangkan alat bantu praktik berbahan wadah minuman bekas pada pengukuran volume benda berbentuk tidak teratur. Sebelum alat bantu praktik diuji cobakan, dilakukan validasi oleh ahli materi dan ahli materi. Hasil rata-rata dari kedua ahli validasi . diperoleh scor 97,05% dengan kategori sangat layak. Uji coba media meliputi uji terbatas yang terdiri dari 12 siswa kelas VII/B dan uji luas yang dilaksanakan pada seluruh siswa kelas VII/B sejumlah 32 siswa. Hasil uji terbatas diperoleh rata-rata 98,3%, dan pada uji luas diperoleh rata-rata 99% dengan predikat sangat layak juga. Setelah dilakukan uji coba siswa diberikan seperangkat alat tes berupa soal yang berkaitan dengan materi pengukuran volume benda yang bentuknya tidak teratur. Hasil test yang diselesaikan oleh siswa setelah menggunakan media yang dikembangkan, siswa yang memperoleh nilai diatas KKM adalah 96%, hal ini menunjukkan bahwa media yang dikembangkan layak digunakan dan dapat membantu pemahaman siswa dalam mempelajari konsep pengukuran volume benda yang berbentuk tidak teratur.